Analisis Terhadap Pelaku Tindak Pidana Eksploitasi Seksual Pada Anak Melalui Media Internet - Eko Nurisman; Jefferson Jefferson (Fakultas Hukum, Universitas Internasional Batam, 2016)
The Internet is a space of information and communication that promise through the boundaries between countries, dissemination and exchange of knowledge worldwide. The presence of the Internet would have a positive impact in the technology of information, the exchange of all data information can be sent or accessed quickly. In addition to having a positive impact the Internet also have negative effects when misused it can even be a crime. The forms of crime today's internet world increasingly varied such as data theft, copyright violations and even crimes against children for sexual exploitation of children. The research method used in this essay is normative and the findings are presented in descriptive analysis to investigate and secondary data in the form of resources and materials related literature of criminal law and the law of information and electronic technology. Based on the results of the study it can be concluded that the Arrangement laws against the crime of sexual exploitation as stipulated in UU ITE currently there are still weaknesses or deficiencies. In Article 27 paragraph (1) there is a term